Предмет:
МатематикаАвтор:
reagan98- 3(2x + 6) = - 3 \times 2x - 3 \times 6 = - 6x - 18
7(x + 4) = 7 \times x + 7 \times 4 = 7x + 28
- 5(2x + 5) - 4x = - 5 \times 2x - 5 \times 5 - 4x = - 10x - 25 - 4x = - 14x - 25
- 2(3x - 4) + 6x = - 2 \times 3x - 2 \times ( - 4) + 6x = - 6x + 8 + 6x = 8
4x + 3(4x - 3) = 4x + 3 \times 4x + 3 \times( - 3) = 4x + 12x - 9 = 16x - 9
3x + 2(5x - 4) = 3x + 2 \times 5x + 2 \times ( - 4) = 3x + 10x - 8 = 13x - 8
Автор:
punkypvlДобавить свой ответ
Предмет:
ГеометрияАвтор:
amarirojasОтветов:
Смотреть
Предмет:
Английский языкАвтор:
chacehumphreyОтветов:
Смотреть
Предмет:
МатематикаАвтор:
kyleighmaldonadoОтветов:
Смотреть